Pooling Water Projects to Move Beyond Project Finance - Haarmeyer, David (World Bank, Washington, DC, 2012)
To date most private sector water projects have been financed on a limited recourse basis, that is, with project cash flows and assets as the main security for lenders. The move from project to corporate (balance sheet) financing is occurring in stages. Financing project debt from the sponsor company's balance sheet exposes that company to significant risk and thus requires a strong and large balance sheet. Designed in part to shield a company's balance sheet, innovative financing structures and instruments are emerging. Ultimately, the goal is for water utilities to raise debt and equity from capital markets on the basis of their own balance sheets, strengthened by a diversified and stable rate-paying customer base. The authors review the new trends.